PENGARUH MARKETING MIX DAN LINGKUNGAN SOSIAL TERHADAP KEPUTUSAN PEMBELIAN ONLINE PAKAIAN WANITA DI KOTA PADANG - Desy Gusrita; Rose Rahmidani (Jurnal Ecogen, 2018)
This study aims to examine the effect of marketing mix and social environment on online women's clothing purchasing decisions in the city of Padang. This research is quantitative descriptive. The population in this study was the people of Padang City who had bought women's clothing online in Padang City using primary data. The sample technique used in this study was purposive sampling with a total sample of 100 respondents. The analytical method used is path analysis using the SPSS version 21 program. For hypothesis testing using a statistical t test with an α level of 5%. The results of this study indicate that 1) Product, price, place, promotion and social environment have a significant effect on purchasing decisions on women's clothing online in Padang City 2) Product has a significant effect on online women's clothing purchasing decisions in Padang City 3) Price has a significant effect on purchasing decisions online women's clothing in Padang City 4) Place has a significant effect on purchasing decisions on women's clothing online in Padang City. 5) Promotion has a significant effect on purchasing decisions on women's clothing online in Padang City. 6) The social environment has a significant effect on women's clothing online purchasing decisions in Padang City. Keyword: Product, Price, Place, Promotion, Social Environment, Purchasing Decision.